Proportion of Traumatic Avascular Necrosis on Hip Joint at Dr. Hasan Sadikin General Hospital Bandung in 2016–2020 - Annisa Nurrizki Baroqah; Undang Ruhimat; Yoyos Dias Ismiarto (Faculty of Medicine Universitas Padjadjaran, 2021)
Background: Traumatic factors affecting the femur such as fractures and dislocations can cause complications in the form of avascular necrosis (AVN), if not treated immediately, AVN is one of the contributors to total hip arthroplasty (THA) usage and disability which will have an impact on productivity and quality of life. Hence, it is necessary to understand the epidemiology of AVN caused by traumatic factors. This study aimed to determine the proportion of traumatic AVN on the hip joint at Dr. Hasan Sadikin General Hospital. Methods: A Descriptive-observational study with a cross-sectional study design was conducted on all patients registered in the medical record database, with a diagnosis of AVN on the hip joint at Dr. Hasan Sadikin General Hospital Bandung in 2016–2020. Traumatic AVN was included and patients with incomplete medical record data were excluded.Results: In total, 210 patients were registered in the medical records and only 56 had complete medical records, and 10.5% (22 of 210) were diagnosed with traumatic AVN of the hip joint, consisting of 14 male with most of the trauma (n=11) caused by AVN were femoral neck fractures and 20 patients were of productive age (18–64 years old). Most of the patients underwent surgical therapy with a THA (n=20).Conclusion: The proportion of AVN on the hip joint caused by trauma is 10.5%. However, this disease should not be underestimated because AVN has the potential to cause disability and impact the quality of life.